Optimasi Rute Terpendek Jalur Distribusi Pupuk Menggunakan Algoritma Artificial Bee Colony (Studi Kasus: PT Bungo Dani Mandiri Utama - Liusman, rio; Winanda, Rara Sandhy (Journal of Mathematics UNP, 2023)
Product distribution involves planning and storing information related to product storage until the product is delivered. PT Bungo Dani Mandiri Utama is a fertilizer distributor that must visit ten retailers in its product distribution. This research aims to test whether the route currently used by PT Bungo Dani Mandiri Utama is optimal or needs improvement. This research is an applied study that uses the Artificial Bee Colony algorithm to solve the fertilizer distribution problem modeled as a Traveling Salesman Problem. From the analysis, the optimal route is obtained, starting from the warehouse, passing Lubuk Beringin, Limbur, Kerakap Island, Rantau Ikil, Mangun Jayo, Tanjung Menanti, Sungai Binjai, SPA Unit 1 Market, Tirta Mulya, Senamat, and back to the warehouse, with a total distance of 330 km. This optimal route is 48 km shorter than the usual route used by PT Bungo Dani Mandiri Utama which covers 378 km.